9.1‐inch stretchable AMOLED display based on LTPS technology. Issue 3 (11th April 2017) - Hong, Jong‐Ho; Shin, Jae Min; Kim, Gun Mo; Joo, Hyejin; Park, Gyung Soon; Hwang, In Bom; Kim, Min Woo; Park, Won‐Sang; Chu, Hye Yong; Kim, Sungchul
Abstract: In this work, we report a freeform shaped active‐matrix organic light‐emitting diode (AMOLED) display based on low‐temperature polycrystalline silicon technology. It was found that our AMOLED, developed with a unique pixel structure, can withstand in various desired shapes featuring its stretchable property with no degradation of image quality and device characteristics. We demonstrated unprecedented convex/concave shape of the 9.1‐inch AMOLED display by low‐temperature thermoforming process. The AMOLED display with freeform design is promising for future display applications such as automotive, Internet of things devices, and wearable electronics. Abstract : We demonstrate a freeform‐shaped AMOLED display based on low‐temperature polycrystalline silicon technology. It was found that our AMOLED can withstand various desired shapes featuring its stretchable property with no degradation of image quality and device characteristics. We successfully fabricated a 9.1‐in. AMOLED display with convex and concave shapes by using a low‐temperature thermoforming process.